Examination of children's body composition and biomotoric features which attended summer football schools - Burak Inan; Onder Dalıoglu (Türk Spor ve Egzersiz Dergisi)
The purpose of the study is to examine body composition and biomotoric specifications of subjects who attendedthe football program for 8 weeks, 3 days a week. In the applied study, 50 subjects were chosen occasionally andvoluntarily out of 125 football players. This study was applied on 8-13 aged male football players who attendedsummer football school in city of Gaziantep. Pre examination of the group was 1 week before 8 week trainingprogram, and post examination was 1 week after 8 week training program. Acquired data were analyzed withSPSS for Windows 16.0 Package software. According to pre and post training program physical andphysiological examination, height, weight, Body Mass Index (BMI), body fat ratio, hand length, total arm length,head circumference, shoulder circumference, waist circumference, hip circumference, biceps circumference, frontarm circumference, calf circumference, shoulder width, elbow width, hip width, hip width, knee width,flexibility measures, hand grip strength (right and left hand) measures, standing long jump, 1 minute shuttle testmeasures, resting hearth rate (RHR), maximal oxygen consumption (VO2 Max) and anaerobic power measureswere found p lt;0.05 level significance. As a result; there were advancements on physical, anthropometric andphysiological values of subjects who attended 8 week summer football school.